Investimento em pesquisa e desenvolvimento (P&D) e desempenho das firmas: um estudo da indústria química - Costa, Francisco Jeferson Alves da (Universidade Federal Rural do Semi-Árido, 2020)
Companies facing an increasingly competitive and dynamic market have increasingly invested in Research and Development (R&D). The objective of this work is to verify the influence of investments in Research and Development on sales in the chemical industry. Using multiple linear regression and correlation as a methodology in panel data, the impact that investment in R&D has on sales was checked and a comparison was made between this impact and that caused by two other variables: number of employees and investment in capital. The sample consists of 60 companies, from 12 countries, from the EU Scoreboard database, analyzed from 2009 to 2018. The results show that investment in R&D has a significant impact on sales in the chemical industry, but that it is less than the other variables. This is because it is not possible to separate investment in R&D from others.
Monografia
Keywords: Indústria química; Pesquisa e desenvolvimento; Vendas; Regressão linear múltipla; Correlação; Chemical Industry; Research and development; Sales; Correlation; Multiple linear regression; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO